Hubungan Personal Hygiene, Kepadatan Hunian, dan Kelembaban dengan Kejadian Skabies pada Santri Putra Pondok Pesantren Al-Aziziyah - Dzikrurrohman, Mochammad Haidyr; Sabariah, Sabariah; Anulus, Ayu; Mulianingsih, Wiwin (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Scabies is a dermatological condition that causes itching sensations on the skin. High prevalence of scabies is often found in places with relatively high population density, such as boarding schools. Additionally, personal hygiene and humidity are other factors influencing the occurrence of scabies. This study aims to determine the relationship between personal hygiene, population density, and humidity with the occurrence of scabies among male students at Al-Aziziyah Islamic Boarding School. The research design used is analytical observational with a cross-sectional study. The sampling technique employed in this research is simple random sampling, with a sample size of 105 respondents calculated using the Slovin formula. The research findings indicate that 63 respondents (60.0%) experienced scabies. The variables of personal hygiene (p < 0.001), population density (p < 0.001), and humidity (p < 0.001) are factors significantly associated with the occurrence of scabies among male students at Al-Aziziyah Islamic Boarding School. There is a significant relationship between personal hygiene, population density, and humidity with the occurrence of scabies among male students at Al-Aziziyah Islamic Boarding School.  Keywords: Scabies, Personal Hygiene, Population Density, Humidity, Al-Aziziyah Islamic Boarding School   ABSTRAK Skabies adalah kondisi dermatologis yang menyebabkan sensasi kulit gatal. Prevalensi skabies yang tinggi ini biasanya dapat ditemukan di tempat dengan jumlah hunian yang cukup tinggi seperti pondok pesantren. Selain itu personal hygiene dan kelembaban menjadi faktor lain yang berpengaruh terhadap kejadian skabies. Penelitian ini bertujuan untuk mengetahui hubungan personal hygiene, kepadatan hunian, dan kelembaban terhadap kejadian skabies pada santri putra di Pondok Pesantren Al-Aziziyah. Jenis penelitian yang digunakan adalah observasional analitik dengan studi penelitian crosssectional. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah simple random sampling, Jumlah sampel dalam penelitian ini seteleh menghitung dengan rumus Slovin adalah 105 sampel. Hasil penelitian menunjukkan  didapatkan santri yang mengalami skabies yaitu sebanyak 63 responden (60,0%). Variabel personal hygiene (p < 0,001), kepadatan hunian (p < 0,001), dan kelembaban (p < 0,001) menjadi faktor yang berhubungan dengan kejadian skabies pada santri putra Pondok Pesantren Al-Aziziyah. Terdapat hubungan signifikan antara personal hygiene, kepadatan hunian, dan kelembaban seseorang dengan kejadian skabies pada santri putra Pondok Pesantren Al-Aziziyah.Mataram. Kata Kunci: Skabies, Personal Hygiene, Kepadatan Hunian, Kelembaban, Pondok Pesantren Al-Aziziyah